2019
DOI: 10.5187/jast.2019.61.6.359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary carbohydrases on productive performance and immune responses of lactating sows and their piglets

Abstract: This study was conducted to evaluate effects of dietary multi-carbohydrases (MCS) in a lactating sow diet on productive performance and immune responses of sows and their piglets. A total of 12 sows (218.37 ± 5.5 kg BW; 2 parity) were randomly assigned to 2 dietary treatments: a diet based on corn-soybean meal (CON) and CON with 0.01% MCS. The MCS contained xylanase (2,700 units/g), β-glucanase (700 units/g), and cellulase (800 units/g). Sows were fed the dietary treatments for 28 days (weaning) after farrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…It has been reported that stress factors during the weaning period induce inflammation in the intestine and serum of weaned pigs, which leads to an increase in typical pro-inflammatory cytokines, such as TNF-α, IFN-γ, IL-β1, IL-6, and TGF-β1 [ 3 ]. In addition, both pro- and anti-inflammatory cytokines play a key role in the regulation of immune responses and intestinal barrier function [ 33 ]. In the present study, YCW supplementation increased the gene expression of some pro-inflammatory cytokines, such as IL-β1 and IL-6, and reduced that of TNF-α; furthermore, the gene expression of anti-inflammatory cytokine, INF-γ, was upregulated in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that stress factors during the weaning period induce inflammation in the intestine and serum of weaned pigs, which leads to an increase in typical pro-inflammatory cytokines, such as TNF-α, IFN-γ, IL-β1, IL-6, and TGF-β1 [ 3 ]. In addition, both pro- and anti-inflammatory cytokines play a key role in the regulation of immune responses and intestinal barrier function [ 33 ]. In the present study, YCW supplementation increased the gene expression of some pro-inflammatory cytokines, such as IL-β1 and IL-6, and reduced that of TNF-α; furthermore, the gene expression of anti-inflammatory cytokine, INF-γ, was upregulated in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Daily visual diarrhea scores of individual pigs (1 = hard and dry normal feces, 2 = well formed, 3 = moist feces, 4 = diarrhea, 5 = watery diarrhea) were recorded for 2 weeks after weaning. The frequency of diarrhea was calculated by counting pens per day with an average diarrhea score over 4 in each pen [ 25 , 26 ]. On day 1, 3, 7, and 14 of the experimental period, one pig was randomly chosen from each pen for blood collection.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, appropriate nutrient supply for weaned pigs is one of essential factors to improve the intestinal health. Several studies reported that some feed additives, such as plant extracts, exogenous enzymes, and GLU, had beneficial effects on growth performance and gut barrier functions of pigs [ 8 , 14 , 15 , 28 ]. In particular, GLU is regarded as one of the most promising performance-enhancing additives with amino acid synthesis properties [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (G:F; gain to feed ratio) were calculated from day 1 to 7, day 8 to 14, day 1 to 14, day 15 to 28, and day 1 to 28. The fecal score of pigs in each pen was visually checked with a score range of 1 to 5 (1 = watery diarrhea, 2 = severe diarrhea, 3 = mild diarrhea, 4 = moist feces, and 5 = normal feces) for the first 2 weeks by two independent experimenters [ 14 ]. The frequency of diarrhea was calculated by counting pen days with a pen average diarrhea score of less than 3.…”
Section: Methodsmentioning
confidence: 99%